2010
DOI: 10.1007/s12031-010-9327-z
|View full text |Cite
|
Sign up to set email alerts
|

A118G Polymorphism of OPRM1 Gene is Associated with Schizophrenia

Abstract: Schizophrenia is ranked among multifactor diseases in whose pathogenesis, besides environmental factors, an interplay of functional polymorphisms of a larger number of candidate genes is involved. Neurodevelopmental abnormities are among the most accepted hypotheses in the etiology of schizophrenia. Recently, the role of oligodendrocytes in the development of the cortex has been cited repeatedly. During their various phases of differentiation oligodendrocytes present on their surfaces diverse receptors, among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
1
21
2
Order By: Relevance
“…P < 0.00001 A group of Czech authors found that the rs1799971 polymorphism of the OPRM1 gene was associated with increased risk of SZ in the male population [51]. However, our results show that the probability of having SZ for those with the G variant of rs1799971 and rs2075572 was decreased, compared to people carrying the A-allele and C-allele, suggesting that the “G” allele of rs1799971 and rs207557 might have a protective effect against SZ.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…P < 0.00001 A group of Czech authors found that the rs1799971 polymorphism of the OPRM1 gene was associated with increased risk of SZ in the male population [51]. However, our results show that the probability of having SZ for those with the G variant of rs1799971 and rs2075572 was decreased, compared to people carrying the A-allele and C-allele, suggesting that the “G” allele of rs1799971 and rs207557 might have a protective effect against SZ.…”
Section: Discussioncontrasting
confidence: 67%
“…The methods used in individual studies, may have limited power to detect a small effect, or small interactions with other relevant polymorphisms. Limited sample size, etiological heterogeneity and clinical heterogeneity may result in inconsistent results showing different associations between the OPRM1 gene and SZ [18,33,51], and therefore, the conclusion of this study may be viewed in this context. Further investigations using larger sample sizes and family-based studies will undoubtedly add further valuable insight into the implications of the relationship between OPRM1 gene polymorphisms and SZ.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data implicate the opioid system in schizophrenia [151] and borderline personality disorder [152], two conditions involving dysregulation of emotional and reward processes. At present, however, animal models of bipolar or borderline personality disorders, or affective dimensions of schizophrenia, are poorly characterized.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…Might oxytocin in autistics subserve, to some degree, positive reinforcement of non-social stimuli, or might epigenetically-based reduction of oxytocin receptor expression (Gregory et al 2009) follow from early social-19 interaction deficits? The µ-opioid system represents another important candidate mechanism, in addition to oxytocin, for neuroendocrine regulation of attachment, given links of allelic variants in the υ-opioid receptor gene OPRM1 with attachment patterns, sensitivity to social rejection, drug dependence, and risk of schizophrenia (Insel 2003;Barr et al 2008;Way et al 2009;Mague and Blendy 2010;Serý et al 2010) and evidence for parent of origin effects influencing phenotypic effects from this gene (Lemire 2005). …”
Section: Autism and Attachmentmentioning
confidence: 99%